Nickel and chromium ions release from stainless steel orthodontic bracket immersed in green betel leaf extract: an in vitro study - Fathiya, Aufa Nida; Trisnawaty, Nety; Anisyah, Ika (Padjadjaran Journal of Dentistry, 2024)
Introduction: Corrosion on stainless steel brackets can occur as a result of using green betel leaves in the oral cavity because they contain a protein that functions as an electrolyte medium, affecting the release of nickel and chromium ions as an early sign of corrosion. The purpose of this study was to analyze the amount of nickel and chromium ions released from a stainless steel orthodontic bracket due to immersion in 25% green betel leaf extract. Methods: The type of research used was laboratory-experimental with a post-test control group design. Tests were carried out on 27 samples, which were divided into three test groups. Brackets were soaked in 25% green betel leaf extract, artificial saliva, and a mixture of 25% green betel leaf extract and artificial saliva for 48 hours and measured using the Atomic Absorption Spectroscopy (AAS). Data analysis in this study using the Shapiro-Wilk normality test and the homogeneity test using the Levene test. The normality and homogeneity test results were fulfilled, thereby permitting the continuation of the analysis with parametric tests, namely the one-way ANOVA test for nickel ions, followed by the Post Hoc Tukey test for nickel ions and the independent T-test for chromium ions. Results: The group soaked in 25% green betel leaf extract showed the highest nickel ion release (16.37 mg/kg), while the highest chromium ion release (18.03 mg/kg) was observed in the group exposed to the mixture of 25% green betel leaf extract and artificial saliva. One-way ANOVA results revealed a significant effect of soaking in green betel leaf extract on nickel ion release (p=0.001), confirmed by Tukey’s Post Hoc test (p=0.001). The T-test indicated significant differences in chromium ion release (p=0.001). Conclusion: Green betel leaf extract has an effect on the release of nickel and chromium ions in stainless steel orthodontic brackets.